PENGERJAAN ABUTMENT 1 PADA PROYEK PEMBANGUNAN FLY OVER BANTAIAN KEC. GUNUNG MEGANG. KAB. MUARA ENIM - Saputra, Ksatria; Rosyad, Farlin (Ensiklopedia of Journal, 2024)
: 1) With the rapid development in South Sumatra Province, the government is implementing development policies in the civil construction sector. This is very necessary to increase development progress in various fields and to provide complete and adequate facilities according to the needs of the users. One of the government's current activities is the KAI Bantaian Flyover Construction Project, Muara Enim District, Gunung Megang District, an activity carried out by the Ministry of Public Works and Public Housing to maintain the quality of roads and bridges. 2) The abutment or bridge head is one of the construction parts found at the ends of the bridge which functions as a support for the building above it and as a retainer for the pyrite pile. In a direction perpendicular to the road axle. This research is qualitative research with the data used as reference material in preparing this Independent Study Proposal, namely Secondary Data. 3) The general form of abutment that is often found on both old and new bridges is in principle all the same, namely as a support for the superstructure, but the most dominant one is in terms of field conditions such as the bearing capacity of the subgrade and the settlement of the seat that occurs. The types of abutments are made from materials such as stone or reinforced concrete with constructions such as walls or walls. 4) In this independent study report the author can conclude: a) The bridge construction project has a length of 50 m. b) The work that the author saw in the field at abutment 1 work on the Fly Over construction project included: 1) Preparatory work, which included preparing tools, such as excavators, vibro rollers, etc., as well as land clearing. 2) Abutment work which includes bore pile foundation work, footing abutment work, abutment neck work and abutment head work.Keywords: Abutment